DAMPAK MEDIA SOSIAL TIKTOK TERHADAP POLA KOMUNIKASI SISWA DI SDN JENANGGER 028 - Masruroh; Dianatul Mustafidah; Ainun Nazilah; Citra Alif Lia Elliana Arianti (JURNAL ILMIAH RESEARCH STUDENT, 2025)
The study aims to analyze the curls' social media impact on the student's communication patterns at the SDN window 208. In the age of civilization 5.0, advances in digital technology have affected various aspects of life, including education. Ticktock, as one of the most popular social media platforms, is widely used by elementary school students to express creativity and interact socially. However, unsupervised tapping may have a negative effect on communication behavior, such as immodest language use and inappropriate imitation of behavior. The study also explfies efforts a teacher can make to enhance the student's speech and modesty. Findings suggest that while ticktock may have benefits, such as encouraging creativity and reducing boredom, it can also interfere with the development of a child's character if not well supervised. Therefore, educators play a vital role in directing the use of social media to have a positive impact on a student's communication pattern.